2021
DOI: 10.1016/j.waojou.2021.100519
|View full text |Cite
|
Sign up to set email alerts
|

Targeting immunoglobulin E in atopic dermatitis: A review of the existing evidence

Abstract: Immunoglobulin E (IgE) plays an essential role in many allergic diseases. This review highlights the role of IgE in atopic dermatitis (AD), a common, chronic, and complex skin inflammation, and the available therapeutic approaches that target IgE in AD. We examine the existing data showing the use of omalizumab, the only biologic anti-IgE therapy available in clinical use, plasma apheresis, and a combination of both therapeutic approaches for the treatment of AD. Existing data on the efficacy of omalizumab in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 82 publications
1
51
1
2
Order By: Relevance
“…At present, there are few research studies on the mechanism of allergic constitution, so that the mechanism is still unclear. However, Caca and Cooke proposed in 1923 the “atopic constitution” that is prone to hypersensitivity reactions due to high IgE levels [ 9 , 10 ]; it is very similar to the allergic constitution proposed by Chinese medicine; and Wollenberg, Thomsen, and Lazarewicz believed that the specific IgE in people with allergies is relatively high [ 11 ]. Based on the above theories, it can be inferred that IgE is closely related to allergies.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are few research studies on the mechanism of allergic constitution, so that the mechanism is still unclear. However, Caca and Cooke proposed in 1923 the “atopic constitution” that is prone to hypersensitivity reactions due to high IgE levels [ 9 , 10 ]; it is very similar to the allergic constitution proposed by Chinese medicine; and Wollenberg, Thomsen, and Lazarewicz believed that the specific IgE in people with allergies is relatively high [ 11 ]. Based on the above theories, it can be inferred that IgE is closely related to allergies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the utility of omalizumab in AD have been inconclusive. 55 Additionally, dupilumab, which targets the shared receptor subunit for IL-4 and IL-13, has shown good results in the treatment of asthma, AD, and CRS. 56 A recent Phase 2 clinical trial has also shown promise in the management of EOE, 14 results that other biologic agents have failed to produce up to this point.…”
Section: Impact Of Treatment Of Comorbid Type 2 Inflammatory Diseasesmentioning
confidence: 99%
“…G4 (n = 10) Animals treated with TPA and TAC at a concentration of 0.1% (w/v) (0.4 mL/animal 1 ) (TAC Group) G5 (n = 10) Animals treated with TPA and TAC-loaded PCL nanocapsules at a drug concentration of 0.1% (w/v) (0.44 mL/animal 1,2,3 ) (NC-1 Group) 1 These volumes were firstly based on the mean weight of each mice group. 2 The drug encapsulation efficiency was also considered for TAC-loaded PCL nanocapsule suspensions. 3 The same volume was used for TAC-loaded and non-loaded PCL nanocapsules (NC-1 and NC-N).…”
Section: Group Treatmentmentioning
confidence: 99%
“…Atopic dermatitis (AD), or eczema, is a dermatological, inflammatory, non-infectious, and chronic disease characterized by long-lasting itching of the affected skin and involves a combination of genetic factors that affect the skin barrier and the immune system [1]. The disease affects about 25% of children and 1 to 3% of adults worldwide [2][3][4]. The common symptoms include skin rashes, erythema, papules, localized exudative lesions, and dry skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation